Veterinary Sanitary Assessment of Meat from Forcedly Slaughtered Animals (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Enter. Currently, attention should be paid to the production of all kinds of animal meat and meat products made from it, and in the process of meat processing, it should be based on new technological aspects. In the decision of the President No. PQ-4576 of January 29, 2020, the rapid development of the livestock industry, the introduction of modern and innovative methods, the increase in the volume of production and the expansion of the types of products, as well as the continuous provision of quality and affordable livestock products to the population produced in local conditions, and the goal of state support for enterprises specialized in animal husbandry is indicated. One of the factors that reduce the quality of livestock products is various diseases among farm animals. At the same time, not only the biological value of meat and meat products, but also, first of all, their veterinary sanitary quality decreases.